GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 192492 species occurrences available in GBIF matching the query: TaxonKey: Mammalia Linnaeus, 1758 Country: Canada HasGeospatialIssue: false HasCoordinate: true. The dataset includes 192492 records from 87 constituent datasets: 35 records from DMNS Mammal Collection (Arctos). 4 records from AMNH Mammal Collections. 6074 records from MVZ Mammal Collection (Arctos). 1 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from Diveboard - Scuba diving citizen science observations. 3 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 2 records from Museum of Zoology, University of Navarra. 7 records from (Table S2) Biometric data, time of ice breakup and carbon isotopic composition of adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 2217 records from UMMZ Mammal Collection. 60 records from FHSM Mammals Collection. 1 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 879 records from CAS Mammalogy (MAM). 29551 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 3483 records from UAM Mammal Collection (Arctos). 258 records from Mammal specimens. 10 records from NCSM Mammals Collection. 121 records from ISU Mammals. 239 records from Mammals Specimens. 160 records from LACM Vertebrate Collection. 2 records from UNSM Vertebrate Specimens. 94 records from Wildlife Sightings. 223 records from Mammal specimens. 3371 records from Geographically tagged INSDC sequences. 1 records from Bioimages. 810 records from University of Alberta Mammalogy Collection (UAMZ). 13 records from UAM Earth Sciences Collection (Arctos). 3 records from Vertebrate Paleontology Division, Yale Peabody Museum. 2 records from Atlantic Reference Centre (OBIS Canada). 363 records from PIROP (Shipboard Surveys). 1799 records from UWBM Mammalogy Collection. 24802 records from HMAP-History pf Marine Animal Populations (CoML). 1 records from Atlantic Canada Conservation Data Centre (OBIS Canada). 8 records from MLZ Mammal Collection (Arctos). 53 records from HSU Wildlife Mammals. 2 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations (OBIS Canada). 2 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 35914 records from Mammalogy Collection - Royal Ontario Museum. 3 records from Museum Victoria provider for OZCAM. 17 records from SBMNH Vertebrate Zoology. 10 records from UCM Mammal Collection (Arctos). 80 records from University of California Museum of Paleontology. 519 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 69 records from TTU Mammals Collection. 68 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 4 records from MSB Host Collection (Arctos). 609 records from NMNH occurrence DwC-A. 413 records from Museum of Comparative Zoology, Harvard University. 25 records from Bay of Fundy Species List (OBIS Canada). 13694 records from Cowan Tetrapod Collection - Mammals. 129 records from NMMNH Mammal. 197 records from NYSM Mammals. 157 records from RBINS collections. 6 records from Fieldjournal.org observation database. 387 records from Mammals housed at MHNG, Geneva. 1009 records from Field Museum of Natural History (Zoology) Mammal Collection. 5 records from UWYMV Mammal Collection (Arctos). 12792 records from SEAMAP - marine mammals, birds and turtles. 1967 records from Paleobiology Database. 36 records from UCLA Donald R. Dickey Bird and Mammal Collection. 81 records from Animal Sound Archive. 311 records from naturgucker. 36 records from Mammal specimens. 525 records from iNaturalist research-grade observations. 27 records from CNMA/Colección Nacional de mamíferos. 35019 records from Mammal specimens. 2354 records from KUBI Mammalogy Collection. 5 records from Mammal tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 120 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 7 records from (Table 3) Concentrations of brominated flame retardants in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 201 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 6 records from (Table 1) Beluga (Delphinapterus leucas) sightings in the eastern Beaufort Sea. 4 records from Australian Museum provider for OZCAM. 61 records from LSUMZ Mammals Collection. 146 records from (Table 2) Expected and observed beluga (Delphinapterus leucas) sightings according to habitat characteristics. 4 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 19 records from (Table 1) Rodent (lemming and vole) densities in 5 study areas in the Canadian Arctic. 3 records from Queensland Museum provider for OZCAM. 3 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 9063 records from MSB Mammal Collection (Arctos). 133 records from CUMV Mammal Collection (Arctos). 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 5 records from South Australian Museum Australia provider for OZCAM. 1505 records from PSM Vertebrates Collection. 65 records from Macaulay Library Audio and Video Collection.
Keywords: GBIF; biodiversity; species occurrences